RESEÑA: Ollero Tassara, Andrés. Bioderecho. Entre la vida y la muerte, Madrid: Thomson-Aranzadi, 2006. - Sánchez González, Santiago (Teoría y Realidad Constitucional, 2007)
The author approaches topics of great constitutional relevance raised by the bioethic, from absortion to the experiments with human embryos.